Service Quality and Customer Satisfaction: Evidence of Nepalese Banks - Shrestha, Prakash (NCC Journal, 2018)
Present research has been conducted to examine the customer satisfaction on service quality of selected commercial banks of Nepal. The study has employed descriptive research design and quantitative study by using survey methodology to deal with customer satisfaction in the context of Nepalese commercial banks. In this study, the data collected through questionnaire from 65 respondents (out of 100 customers of commercial banks) has been used for analysis. A detail study has been done on the basis of five dimensions as suggested by Parasuraman, Zeithamal and Berry (1988). They are reliability, responsiveness, assurance, empathy and tangibles. The result of the study indicated that the overall customers are satisfied with service quality of the commercial banks. Hence the level of customer satisfaction of the commercial banks on the basis of service quality can be considered satisfactory.NCC JournalVol. 3, No. 1, 2018, Page: 121-133